Using variable interfacial adhesion characteristics within a composite to improve flexural strength and decrease fiber volume. (8th September 2018) - Stojcevski, Filip; Randall, James D.; Henderson, Luke C.
Abstract: This paper investigates the impact of using amine functionalised fibers in composite "hybrid" laminates to improve interfacial shear strength (IFSS) and reduce laminate weight. A comparison of single fiber fragmentation testing (SFFT) and short beam shear testing (SBS) showed that 103.6% improvements of IFSS at a single fiber level only translate to a 23.3% improvement in SBS testing. However, localised use of both functionalised and non-functionalised T300 fibers in a "hybrid interface" laminate improved IFSS by 56.7%. Hence this study shows that careful placement of fibers and localised manipulation of the interface characteristics can be used to great effect when designing a composite material. Ultimately, the use of a hybrid interface approach was able to provide a weight reduction of 11.27% while not sacrificing flexural strength compared to the baseline T300 fibers.